Autoregulation of kinase dephosphorylation by ATP binding to AGC protein kinases - Chan, Tung O (Landes Bioscience, 2012)
AGC kinases, including the three Akt (protein kinase B) isoforms, protein kinase A (PKA) and all protein kinase C (PKC) isoforms, require activation loop phosphorylation (threonine 308 in Akt1) as well as phosphorylation of a C-terminal residue (serine 473 in Akt1) for catalytic activity and phosphorylation of downstream targets. Conversely, phosphatases reverse these phosphorylations. Virtually all cellular processes are affected by AGC kinases, a circumstance that has led to intense scrutiny of the molecular mechanisms that regulate phosphorylation of these kinases. Here, we review a new layer of control of phosphorylation in Akt, PKA and PKC pointing to ATP binding pocket occupancy as a means to decelerate dephosphorylation of these and, potentially, other kinases. This additional level of kinase regulation opens the door to search for new functional motifs for the rational design of non-ATP-competitive kinase inhibitors that discriminate within and between protein kinase families.